Test–retest variability of [11C]ABP688 estimates of metabotropic glutamate receptor subtype 5 availability in humans - Smart, Kelly; Cox, Sylvia M. L.; Nagano‐Saito, Atsuko; Rosa‐Neto, Pedro; Leyton, Marco; Benkelfat, Chawki (Synapse (New York, N.Y.), 2018)
[11C]ABP688 is a positron emission tomography (PET) radioligand that binds selectively to metabotropic glutamate type 5 receptors (mGluR5). The use of this tracer has identified receptor binding changes in clinical populations, and has been informative in drug occupancy studies. However, previous studies have found significant increases in [11C]ABP688 binding in the later scan of same‐day comparisons, and estimates of test‐retest reliability under consistent scanning conditions are not available. The objective of this study was to assess the variability of [11C]ABP688 binding in healthy people in scans performed at the same time of day. Two [11C]ABP688 scans were acquired in eight healthy volunteers (6 women, 2 men) using a high‐resolution research tomograph (HRRT). Scans were acquired 3 weeks apart with start times between 10:00am and 1:30pm. Mean mGluR5 binding potential (BPND) values were calculated across cortical, striatal and limbic brain regions. Participants reported on subjective mood state after each scan and blood samples were drawn for cortisol analysis. No significant change in BPND between scans was observed. Variability in BPND values of 11–21% was observed across regions, with the greatest change in the hippocampus and amygdala. Reliability was low to moderate. BPND was not statistically related to scan start time, subjective anxiety, serum cortisol levels, or menstrual phase in women. Overall, [11C]ABP688 BPND estimates show moderate variability in healthy people. Reliability is fair in cortical and striatal regions, and lower in limbic regions. Future research using this ligand should account for this in study design and analysis. Test–retest variability of BPND estimates for the PET radiotracer [11C]ABP688 were analyzed in eight healthy volunteers scanned at the same time of day 3 weeks apart. Variability was moderate overall, lower than has been reported in same‐day comparisons and less within the prefrontal cortex and striatum than in limbic regions.